Panorama of Cal Poly Campus - Frank Aston::::::photographer::: (1929)
Hand tinted panorama of Cal Poly Campus, 1929 or 1930. Taken before ground broken for Chase Hall, after construction of Jespersen Dorm in late 1929. Looking east from Radio Tower hill.